Avian embryonic coronary arterio‐venous patterning involves the contribution of different endothelial and endocardial cell populations. Issue 5 (13th January 2018) - Palmquist‐Gomes, Paul; Guadix, Juan Antonio; Pérez‐Pomares, José M.
Abstract : Background: Coronary vasculature irrigates the myocardium and is crucial to late embryonic and adult heart function. Despite the developmental significance and clinical relevance of these blood vessels, the embryonic origin and the cellular and molecular mechanisms that regulate coronary arterio‐venous patterning are not known in detail. In this study, we have used the avian embryo to dissect the ontogenetic origin and morphogenesis of coronary vasculature.Results: We show that sinus venosus endocardial sprouts and proepicardial angioblasts pioneer coronary vascular formation, invading the developing heart simultaneously. We also report that avian ventricular endocardium has the potential to contribute to coronary vessels, and describe the incorporation of cardiac distal outflow tract endothelial cells to the peritruncal endothelial plexus to participate in coronary vascular formation. Finally, our findings indicate that large sinus venosus‐independent sections of the forming coronary vasculature develop without connection to the systemic circulation and that coronary arterio‐venous shunts form a few hours before peritruncal arterial endothelium connects to the aortic root.Conclusions: Embryonic coronary vasculature is a developmental mosaic, formed by the integration of vascular cells from, at least, four different embryological origins, which assemble in a coordinated manner to complete coronary vascular development. Developmental Dynamics 247:686–698, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Embryonic coronary vasculature forms from multiple vascular sources. Endocardial‐derived and proepicardial‐derived coronary endothelium simultaneously vascularize the developing heart. During early coronary development only prospective coronary veins remain connected to the systemic blood flow. A relevant part of prospective coronary arterial and capillary sections remain disconnected from the systemic blood flow during heart coronary vascularization. Endothelial cells from the distal cardiac outflow tract are identified as a new source of coronary endothelium.